2016
DOI: 10.1128/aem.01132-16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Specimen Collection Methodologies and Storage Conditions on the Short-Term Stability of Oral Microbiome Taxonomy

Abstract: Community profiling of the oral microbiome requires the recovery of quality sequences in order to accurately describe microbial community structure and composition. Our objective was to assess the effects of specimen collection method, storage medium, and storage conditions on the relative abundance of taxa in saliva and plaque identified using 16S rRNA genes. We also assessed short-term changes in taxon composition and relative abundance and compared the salivary and dental plaque communities in children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 38 publications
(40 reference statements)
1
25
0
Order By: Relevance
“…Using nitrate supplementation as selective pressure for bacteria capable of nitrate reduction, several studies found proliferation of Veillonella [205], Streptococcus [204], Neisseria [115], Haemophilus [204], and Rothia species[115], all previously identified as high nitrate reducers. Yet, despite these varied attempts, there remains a high degree of variability in results depending on numerous methodological factors[206], including source and sampling of sample (saliva versus oral wash versus tongue scraping), direct sampling versus culture, and choice of 16S variable region for sequencing.…”
Section: The Oral Microbiome and Bacterial Nitrate Reductionmentioning
confidence: 99%
“…Using nitrate supplementation as selective pressure for bacteria capable of nitrate reduction, several studies found proliferation of Veillonella [205], Streptococcus [204], Neisseria [115], Haemophilus [204], and Rothia species[115], all previously identified as high nitrate reducers. Yet, despite these varied attempts, there remains a high degree of variability in results depending on numerous methodological factors[206], including source and sampling of sample (saliva versus oral wash versus tongue scraping), direct sampling versus culture, and choice of 16S variable region for sequencing.…”
Section: The Oral Microbiome and Bacterial Nitrate Reductionmentioning
confidence: 99%
“…This approach has exploded in popularity with advances in sequencing throughput such that it is now possible to characterize numerous samples with thousands of sequences per sample. Many factors can impact how a natural community is represented by the sequencing data including the method of acquiring samples (4–8), storage conditions (4–6, 9–12), extraction methods (13), amplification conditions (8, 14, 15), sequencing method (15–17), and analytical pipeline (15, 18–20). The increased sampling depth that is now available relative to previous Sanger sequencing-based methods is expected to compound the impacts of an investigator’s choices and the interpretation of their results.…”
Section: Introductionmentioning
confidence: 99%
“…The V6 region of the 16s rRNA gene was amplified in the sample set, using primers and protocols described elsewhere [23,24]. The forward and reverse primer sequences mapped to the 967-985 (CAACGC-GARGAACCTTACC) and 1078-1061 (ACAACACGAGCTGACGAC) on the Escherichia coli 16s rRNA segment, with unique 8-nucleotide error-correcting barcodes added to the reverse primer for each sample.…”
Section: Amplicon Sequencing For Characterization Of Salivary Microbimentioning
confidence: 99%